Hematologic Findings in Children With Brucellosis: Experiences of 622 Patients in Eastern Turkey. Issue 6 (August 2016) - Karaman, Kamuran; Akbayram, Sinan; Bayhan, Gülsüm İ.; Dogan, Murat; Parlak, Mehmet; Akbayram, Hatice T.; Geylan, Hadi; Garipardic, Mesut; Oner, Ahmet F.
Abstract : The aim of the present study was to present the hematologic findings of 622 cases diagnosed with acute brucellosis. Medical records of children with brucellosis, admitted to Yuzuncu Yil University Hospital over a 6-year period, were analyzed retrospectively. Three hundred ninety-seven (63.8%) patients were male and 225 (36.2%) were female. The mean age was 11 years (range, 1 to 16 y). The mean hematologic values were as follows: hemoglobin 9.4 (3.4 to 17) g/dL, hematocrite 28% (12% to 50%), leukopenia 2.8 (1.1 to 33)×10 9 /L, leukocytosis 13.7 (1.1 to 33)×10 9 /L, and platelets 79 (3 to 972)×10 9 /L. An overall 28.6% of patients were found to have anemia, alone or in combination with leukopenia or thrombocytopenia. Sixteen percent of patients had thrombocytopenia, 13.9% had leukopenia, 7.7% had pancytopenia, and 4% had both leukopenia and thrombocytopenia. Hematologic complications such as anemia, thrombocytopenia, and leukopenia are more frequently seen in acute brucellosis cases. However, acute brucellosis should also be considered in the differential diagnosis in the presence of other hematologic abnormalities such as severe thrombocytopenia, bicytopenia, and pancytopenia.